2021
DOI: 10.1002/smll.202004552
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Emissive Upconversion Nanoparticles: Material Design and Applications

Abstract: Upconversion nanoparticles (UCNPs) have gone beyond traditional fluorophores in a lot of fields due to the outstanding features such as sharp excitation and emission bands, chemical and photo stability of high quality, low auto fluorescence, and high tissue permeation depth of the near‐infrared irradiation light used for excitation. Conventional UCNPs carrying single/multiple emissions under a single excitation wavelength can be only employed in concurrent activation, orthogonal emissive upconversion nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 106 publications
(162 reference statements)
0
42
0
Order By: Relevance
“…[ 12 ] Studies have shown that the morphology of the materials has a great influence on the optical, magnetic, and electrical properties. [ 13–15 ] Despite the achievements, a study on constructing a NaYF 4 library for systematically evaluating the influence of morphologies and sizes on the resulting properties is still absent.…”
Section: Resultsmentioning
confidence: 99%
“…[ 12 ] Studies have shown that the morphology of the materials has a great influence on the optical, magnetic, and electrical properties. [ 13–15 ] Despite the achievements, a study on constructing a NaYF 4 library for systematically evaluating the influence of morphologies and sizes on the resulting properties is still absent.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the inter-shell energy transfer effectively depopulates the 6 P 7/2 excited state of Gd 3+ ; the depopulation of Gd 3+ ( 6 P 7/2 ) facilitates the energy transfer from Tm 3+ ( 1 I 6 ) to Gd 3+ ( 6 P 7/2 ) that speeds up the depopulation of 1 I 6 excited state; then the rapid depopulation of upper energy state 1 I 6 in turn promotes the stepwise five-photon upconversion process from the lower energy states of Tm 3+ . These discoveries provide a deeper mechanistic understanding of the fundamental EMU process in lanthanide NCs involving energy management 3,[68][69][70][71][72][73] on the nanometer-length scale, which may pave a new way to control or modify the upconversion emissions of lanthanide NCs and consequently contribute to their frontier bioapplications. [74][75][76][77][78][79][80][81]…”
Section: Discussionmentioning
confidence: 98%
“…Lanthanide-doped upconversion nanocrystals (UCNCs) have become ideal candidates for applications in biological labeling and imaging areas owing to their attractions such as sharp emission peaks, long luminescence lifetimes, high photostability, low toxicity, and deep light penetration depth, etc. [1][2][3][4] Notably, the most common activators, applied to achieve efficient UC luminescence (UCL), are restricted to Er 3+ , Tm 3+ , and Ho 3+ due to the fact that their ladder-like energy levels ensure effective sensitization by Yb 3+ ions. 5 Nonetheless, a series of lanthanide ions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The so-called upconversion process is a nonlinear optical process that converts long-wavelength stimulation light with lower energy into short-wavelength emission with higher energy that can be ascribed to an anti-Stokes mechanism. [27][28][29][30][31][32][33] The upconversion mechanism and process have been extensively studied in the past decade, and can be divided into five main classes, which include excited state absorption, energy transfer, photon avalanche, cooperative sensitization upconversion, and energy migration upconversion. [34][35][36][37] Up to now, UCNPs with well controlled shape, size, as well as improved luminescence efficiency could be synthesized by various developed methods such as the chemical coprecipitation, [38][39][40] thermal decomposition, [41][42][43][44][45] and hydro(solvo)thermal.…”
Section: Properties Of Ucnps With Switchable Emissionmentioning
confidence: 99%